The Effect of Direct Democratic Participation on Citizens’ Political Attitudes in Switzerland: The Difference between Availability and Use - Kern, Anna (2017)
According to advocates of direct democracy, it is important to involve citizens more directly in political decision-making processes in order to create a democratic linkage between citizens and the political system. Indeed, some studies have demonstrated that citizens who live in direct democracies have higher levels of trust in political institutions and a higher sense of political efficacy. However, not all empirical evidence confirms this relationship. In a recent article on Switzerland, it was shown that, while the availability of direct democratic rights enhances trust in political institutions, using those rights actually initiates distrust. In this paper I expand the analysis of Bauer and Fatke (2014) and test whether the different effects of availability of direct democratic rights and the frequency of their use also hold for broader measures of trust in political institutions and political efficacy. I find that, even though an increased use of direct democratic measures is associated with lower levels of confidence in authorities on the cantonal level, this relationship is no longer apparent when applying a more comprehensive measurement of trust in political institutions.